A preliminary study on the correlation of frequency components between finger PPG and radial arterial BP waveforms - Hsin Hsiu; Chia-Liang Hsu; Tsung-Lin Wu (2009 International Conference on Biomedical and Pharmaceutical Engineering, 2009)
Objective: Blood pressure (BP) waveform has important meaning in the study of circulatory diseases, but its noninvasive assessment is not sufficiently user-friendly for practical applications. In the present study, we try to build up a user-friendly PPG measurement system, and study the correlation between radial BP and finger photoplethysmography (PPG) waveforms Methods: User-friendliness of a self-made PPG measurement system was improved by applying an appropriate contacting pressure on the measured finger and adapting a hand-shape mold for the finger to put on. Finger PPG and radial-artery BP signals were then measured simultaneously and noninvasively on healthy volunteers (n=?). In frequency-domain analysis performed on each 1-minute recorded data sequence, the linear regression was applied to the calculated amplitude ratios between BP and PPG waveforms. Results: After a series of testing, the PPG measurement system was found to be user-friendly and has a good reproducibility in the frequency components within the measured PPG waveform. The BP-PPG regression of amplitude ratios were all significant (R 2 values all ¿0.72) for the first three harmonics. Conclusion: In the present study we built up a user-friendly PPG measurement system, and developed a frequency-domain analysis method to study the correlation between BP and PPG waveforms. We hope that the noninvasive PPG measurement system and the frequency-domain waveform analysis can provide an alternative and a more user-friendly method to reconstruct the radial BP waveform, and hence broaden the application of BP waveform analysis, which may bring deeper understanding for important circulatory diseases.